Effectiveness of an educative intervention developed on pupils of Compulsory Secondary Education´s first course in Madrid about social gender estereotype - Sara Sánchez Castro; Ana B. Salamanca Castro; Estela Maeso Fernández; Amelia Amézcua Sánchez; Diana de la Fuente Aparicio; Pedro Caballero Álvarez (Fundación para el Desarrollo de la Enfermería, 2011)
Violence against women frequently focus on people who live together, leaving aside violence exert in those couples where individual do not live together, more common in adolescents, and which has been called "dating violence". Adolescents are a poblational group with some specific risk factors, due to, among other things, the fact that their behavior is determinated by a competitive, liberate society, where there is still gender stereotypes, shaped, as Glick and Fiske noticed, by an ambivalent sexism, where stereotypes are not only hostile but also benevolent, but which, anyway, predispose towards violent attitudes both physical and psychological. Numerous studies about these subject show that the way to prevent this kind of violence is acting from education; actually, in the subject Education for citizenship special attention is paid on the women and men equality. Many studies have developed interventions to prevent dating violence through education in gender equality, but these studies have evaluated their intervention developed by the students and teachers valuation, the intervention effectiveness was not really measured. Thus, we think it would be interesting to evaluate, with a validated instrument as the Ambivalent Sexism Inventory for adolescents the effectiveness of an educative intervention focused on reduce the sexist prejudice both hostile and benevolent in a population of pupils who attend to first course of Compulsory Secondary Education. To achieve this, we have developed a group clinical trial where experimental group will attend to four educative sessions focused on reduce sexist prejudice, and the control group will receive the equality formation compulsory in this cycle. Randomization will be realized by centers, so pupils will belong to experimental or control group depending on which center they attend to.